2017
DOI: 10.1515/jtim-2017-0022
|View full text |Cite
|
Sign up to set email alerts
|

Is aortic aneurysm preventable?

Abstract: Abdominal aortic aneurysm (AAA) is a chronic inflammatory condition, triggered by the local accumulation of macrophages, oxidative stress and damage to the aortic wall. Pro-inflammatory eicosanoids seem to play a significant role in AAA. The pro-inflammatory events seen in AAA could be due to a deficiency of anti-inflammatory eicosanoids such as lipoxin A4 (LXA4), resolvins, protectins and maresins as a result of reduced tissue concentrations of their precursors: arachidonic acid (AA), eicosapentaenoic acid (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Many previous studies have also documented the inhibitory effects of quercetin on cyclooxygenase-2 (COX-2) expression [ 18 ] and angiogenesis [ 19 ]. Moreover, the AAA development has been characterized by the increased expression of COX-2, and the inactivation of COX-2 may lead to a new approach to prevent AAA expansion [ 20 22 ]. It is worth mentioning that rigorous analyses reveal that COX-2 upregulation is transcriptional and is associated with the hypoxia-inducible factor 1 α (HIF-1 α ) induction [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many previous studies have also documented the inhibitory effects of quercetin on cyclooxygenase-2 (COX-2) expression [ 18 ] and angiogenesis [ 19 ]. Moreover, the AAA development has been characterized by the increased expression of COX-2, and the inactivation of COX-2 may lead to a new approach to prevent AAA expansion [ 20 22 ]. It is worth mentioning that rigorous analyses reveal that COX-2 upregulation is transcriptional and is associated with the hypoxia-inducible factor 1 α (HIF-1 α ) induction [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ang II has a proinflammatory effect and can increase inflammatory markers and the production of free radicals, triggering inflammatory events, which may be the basis of Ang II-mediated induction of AAA. 42 Because ApoE−/− mice lack the ApoE gene and lipids and cholesterol are more likely to accumulate in the aorta, leading to more severe atherosclerosis and inflammation, Ang II-infused ApoE−/− mouse models are commonly used in preclinical AAA studies. 43 Our study showed that the aortic wall was damaged and elastin was degraded in the AAA group.…”
Section: Discussionmentioning
confidence: 99%
“…In consequence, pro-inflammatory AA seems to play an important role in AAD. The pro-inflammatory response observed in AAD could be due to the lack of anti-inflammatory AA results 107 . Therefore, it is necessary to investigate whether the combined application of PUFA is more suitable for the prevention of AAD in humans.…”
Section: Lipid Metabolism In Aadsmentioning
confidence: 99%
“…Low serum EPA levels and EPA/AA ratio were associated with the size and growth rate of AAA [121]. The protective effects and underlying mechanisms of EPA in AAA have been identified (Figure 4): (1) increased anti-inflammatory property of macrophages due to lessened inflammatory factor such as MMP2 and MMP9 levels [122][123][124] (2) attenuated of mesenchymal stem cell (MSC) dysfunctions [125] (3) suppressed the weakening of the vascular wall by inhibiting the elastin fiber degradation caused by nicotine [126] (4) inhibition of endothelial cell-mediated inflammatory factors [107]. AAA is associated with inflammation and oxidative stress, the latter of which contributes to activation of macrophages, a prominent cell type in AAA.…”
Section: Omega -3 Polyunsaturated Fatty Acidmentioning
confidence: 99%